Emergence of transnational clusters: Evidence from the Slovak automotive industry - Peter Zámborsky (Journal for East European Management Studies, 2012)
We explore the evolution of automotive clusters in Slovakia from the emergence to growth stages of their life cycles and investigate how the clusters spill over national borders. We also analyze how clusters and their transnationality affect firm competitiveness. Our findings suggest that although the clusters have an overall positive impact on competitiveness of participating firms, it is not the transnational cluster linkages that matter most for the emerging clusters. Linkages with firms in the same group in Central Europe matter more for competitiveness than shared institutions and linkages arising from geographic proximity. – – Wir beforschen die Entwicklung der Automobilbranche in der Slowakei von ihrer Entstehung bis zur Wachstumsphase ihres Lebenszyklus und untersuchen wie die Cluster nationale Grenzen überschreiten. Wir analysieren zudem, wie die Cluster und ihre Transnationalität sich auf die Wettbewerbsfähigkeit der Unternehmen auswirken. Unsere Ergebnisse deuten daraufhin, dass obwohl die Cluster eine generell positive Auswirkung auf die Wettbewerbsfähigkeit der beteiligten Firmen haben, es nicht die transnationalen Verbindungen zwischen den Clustern ist, die die größte Bedeutung für die neu entstehenden Cluster haben. Verbindungen mit Firmen der gleichen Gruppe in Zentraleuropa sind bedeutsamer für die Wettbewerbsfähigkeit als gemeinsame Institutionen und Beziehungen, die auf geografischer Nähe beruhen.
Keywords: 650; cluster life-cycle; transnationality; competitiveness; automotive